Distinct spatial and temporal roles for Th1, Th2, and Th17 cells in asthma - Luo, Weihang; Hu, Jindong; Xu, Weifang; Dong, Jingcheng (Frontiers in Immunology, 2022)
Immune response in the asthmatic respiratory tract is mainly driven by CD4+ T cells, represented by Th1, Th2, and Th17 cells, especially Th2 cells. Asthma is a heterogeneous and progressive disease, reflected by distinct phenotypes orchestrated by Τh2 or non-Th2 (Th1 and Th17) immune responses at different stages of the disease course. Heterogeneous cytokine response within the same Th effector state in response to changing conditions in vivo and interlineage relationship among CD4+ T cells shape the complex immune networks of the inflammatory airway, making it difficult to find one panacea for all asthmatics. Here, we review the role of three T helper subsets in the pathogenesis of asthma from different stages, highlighting timing is everything in the immune system. We also discuss the dynamic topography of Th subsets and how this result in pathogenetic memory Th cell as a new player in asthma.